USO DE ADITIVOS AO FLUIDO DE LAVAGEM PERITONEAL PARA A PREVENÇÃO DE ADERÊNCIAS ABDOMINAIS E A OTIMIZAÇÃO DA CICATRIZAÇÃO DA PAREDE ABDOMINAL - Dheywid Karlos Mattos Silva (2023)
SILVA, D. K. M. Use of additives to the peritoneal lavage fluid to prevent abdominal adhesions and optimize the healing of the abdominal wall. 2018. DOCTORATE DEGREE – Graduate Program in Veterinary Sciences. Faculty of Veterinary Medicine and Animal Science. Universidade Federal de Mato Grosso do Sul, Campo Grande, MS, 2023. Adhesion is the union of two or more anatomically separated structures through fibrous tissue as a result of an inflammatory process. When it occurs in the abdominal cavity, it can cause pain and organ dysfunction. In its prevention, abdominal lavage is used, but there is no consensus on the most appropriate fluid composition. In this way, we tested and compared different solutions added or not to the drugs most frequently used in intraoperative routines. One hundred and twenty-six male Wistar rats were allocated into 15 groups of six rats and three groups of 12 rats. All animals were submitted to surgical cecopexy. In a first step, solutions of Ringer Lactate, 0.9% NaCl and distilled water were compared. Then, abdominal lavage solutions (distilled water + drug) containing: (1) local anesthetics (lidocaine and bupivacaine); (2) antimicrobials (gentamicin, enrofloxacin and ceftriaxone); (3) steroidal anti-inflammatory drugs (dexamethasone, methylprednisolone and hydrocortisone); (4) NSAIDs (robenacoxib and flunixin meglumine); (5) anticoagulant (heparin); (6) Glucose (5%, 10% and 25%). Blood and peritoneal lavage samples were collected preoperatively (t=-1) and after euthanasia (t=21) when a standardized flap was also extracted from the abdominal wall around the surgical scar. The solutions were compared in terms of: (1) reduction of abdominal discomfort (behavioral parameters and Grimace Scale); (2) peritoneal fluid composition (white blood cell count and glucose measurement, albumin, sodium, and total protein dosages); (3) quantification of adhesion formation; (4) scar maturity (histopathology); (5) strength of the abdominal wall scar (microtensile test). With the exception of the heparin-treated group, all other lavage solutions contributed to the patients' recovery and the solution with distilled water reduced serum sodium levels. It is concluded that the abdominal lavage solutions tested reduce postoperative morbidity, the choice of the type of solution and additive do not interfere with surgical recovery, except for those added with heparin. Furthermore, it is suggested that the use of distilled water should be accompanied by the monitoring of serum sodium. Keywords: Glucose, leucocytes, peritoneum, prophylaxis, rats.